Assessment of oxidative stress in dairy cows supplemented prepartum with vitamin E and selenium with reference to retention of fetal membranes - GUPTA, SANDEEP KUMAR; KUMAR, HARENDRA; MORE, T (The Indian Journal of Animal Reproduction, 2023)
The occurrence of retention of fetal membranes (RFM), the levels of lipid peroxide LPO, indices of oxidative stress) and plasma cortisol were studied in cows following prepartum supplementation of 1100 JU Vit. E and 30 mg selenium. The prepartum supplementation of vit. E and selenium alleviated the incidence of RFM from 12 to 0%. The injection of vit. E and selenium significantly (P < 0.01) reduced the LPO levels at 0 wk prepartum. A significant (P < 0.01) increase in LPO levels (3.67±0.16 Vs 2.46±0.07 nanomoles MDNmg of Hb) was noticed from 3 to 0 wk inthose cows which experienced RFM. Furthermore, a significant (P < 0.05) increase was observed in plasma cortisol level (60.50±4.33 Vs 25.64±6.26 ng/ml) at prepartum period in RFM cows as compared to non-RFM. It can be concluded that the prepartum supplementation of Vit. E and Se reduced the levels of LPO and thereby the incidence of RFM.